Inflation uncertainty, disagreement and monetary policy: Evidence from the ECB Survey of Professional Forecasters - Alexander Glas; Matthias Hartmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analyze the determinants of average individual inflation uncertainty and disagreement based on data from the European Central Bank's Survey of Professional Forecasters. We empirically confirm the implication from a theoretical decomposition of inflation uncertainty that disagreement is an incomplete approximation to overall uncertainty. Both measures are associated with macroeconomic conditions and indicators of monetary policy, but the relations differ qualitatively. In particular, average individual inflation uncertainty is higher during periods of expansionary monetary policy, whereas disagreement rises during contractionary periods.
Keywords: E31; E52; E58; 330